2012
DOI: 10.1155/2012/148387
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy in Liver Transplantation: The Future Has Arrived

Abstract: In the last two decades, laparoscopy has revolutionized the field of surgery. Many procedures previously performed with an open access are now routinely carried out with the laparoscopic approach. Several advantages are associated with laparoscopic surgery compared to open procedures: reduced pain due to smaller incisions and hemorrhaging, shorter hospital length of stay, and a lower incidence of wound infections. Liver transplantation (LT) brought a radical change in life expectancy of patients with hepatic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…6 In another study, laparoscopic gastrectomy showed fewer inflammatory and immunologic reactions compared to open gastrectomy. 10 In contrast to the increased role of diagnostic and therapeu-tic laparoscopy in liver transplantation, 7 only one case report was published; laparoscopy assisted distal gastrectomy in liver transplantation patient. No more report has been reported since then.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 In another study, laparoscopic gastrectomy showed fewer inflammatory and immunologic reactions compared to open gastrectomy. 10 In contrast to the increased role of diagnostic and therapeu-tic laparoscopy in liver transplantation, 7 only one case report was published; laparoscopy assisted distal gastrectomy in liver transplantation patient. No more report has been reported since then.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the increased role of diagnostic and therapeutic laparoscopy in liver transplantation, 7 only one case report was published; laparoscopy assisted distal gastrectomy in liver transplantation patient. No more report has been reported since then.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of laparoscopy following solid organ transplant has changed over the years. Initially considered not suitable after transplantation, laparoscopy has acquired acceptance in kidney‐transplanted patients first, given the extraperitoneal nature of the approach and the lower risk of thick intraperitoneal adhesions . Over time, minimally invasive procedures have been increasingly accepted also in liver‐transplanted patients, including laparoscopic lymphocele drainage, laparoscopic adhesiolysis, and laparoscopic repair of incisional hernia .…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, most surgeons would opt for an open laparotomy in children who underwent liver transplant and need further abdominal surgery. However, recently this view has been challenged by some authors, who do not consider laparoscopy after liver transplantation an absolute contraindication, but actually a possible indication in selected cases .…”
mentioning
confidence: 99%